HUBUNGAN ANTARA GROWTH MINDSET DENGN ACADEMIC BURNOUT PADA SISWA SMK NEGERI 6 KOTA JAMBI - Kheylyla; Muhammad Ferdiansyah; Muhammad Alridho Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between Growth Mindset and Academic burnout in students of SMK Negeri 6 Jambi City. Academic burnout is characterized by emotional exhaustion, cynicism towards learning, and decreased academic efficacy due to prolonged study pressure. Growth Mindset is the belief that intelligence can be developed through effort, appropriate strategies, and input from others. This study used a quantitative approach with a correlational design. The sample consisted of 253 students selected using a simple random sampling technique. The research instrument was a Likert scale questionnaire. The results of the validity test on 32 respondents showed that 18 of the 21 Growth Mindset items and 28 of the 31 Academic burnout items were declared valid (r table = 0.349). The reliability test showed a Cronbach's Alpha value of 0.869 for Growth Mindset and 0.930 for Academic burnout, thus declared reliable. The results of the Pearson correlation analysis showed a significant negative relationship between Growth Mindset and Academic burnout (r = −0.212; p = 0.001 < 0.05). The higher a student's Growth mindset, the lower the level of Academic burnout they experience.